GAYA KEPEMIMPINAN INFORMAL PADA UPT PEMASYARAKATAN - Rifky Ananda Tarigan; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
In society and in organizational environments, both formal and informal, there is always someone who is considered more than others, such a person is generally referred to as a leader. The existence of a leader is absolutely necessary in needing a leader figure. A leader needs to appear on behalf of his group as a place to take risks when there is pressure on a group and as a place to put power. The leader will also coordinate the group in carrying out every activity that will be made or a product. In the figure, a leader must also apply the principles and style of good leadership, because a leader not only brings personality but a group that certainly has different characters from one another. So in an association between individuals who form a group and stay in one place or move, it must have a leader figure who is able to bring them to a mutually agreed goal. For this reason, in order for a leader to be able to bring the group he leads, he must be trained and know the values of leadership and apply them to the group.